Systematic redescription of Solen (Ensisolen) tehuelchus and Ensis macha (Bivalvia: Solenoidea) from Argentina, southwestern Atlantic Ocean - Giacomino, Sebastián; Signorelli, Javier H. (Zootaxa, 2021)
In the present study, bivalves belonging to the superfamily Solenoidea that inhabit the Argentinean Sea are redescribed. The specimens studied in this work were collected by scuba diving in the Gulf of San José, Argentina. Additional specimens from different malacological collections were revised to update the geographical distribution of valid species. According to the literature, there exist two species for the “Argentinean” and “Magellan” biogeographical provinces. However, ten nominal taxa, with uncertain taxonomic status, have been mentioned for the study area. Field work, local collection survey and type material examination allow confirming two valid species: Solen (Ensisolen) tehuelchus Hanley (Solenidae) and Ensis macha (Molina) (Pharidae). A morphological comparison between S. tehuelchus and S. gaudichaudi Chenu and S. obliqua Spengler is provided as well type locality, repository and synonymy list. The type material of all related species are illustrated whenever possible. Establishing the valid names of these species is the first step towards more integrative studies including genetic and zoogeographical analyses.